IMPROVING THE BUSINESS PROCESS BY FINDING ADDITIONAL RESOURCES NEEDED TO INCREASE FINANCIAL POTENTIAL OF INSURANCE COMPANY - B. V. Samorodov; G. M. Azarenkova; O. G. Golovko (Фінансово-кредитна діяльність: проблеми теорії та практики, 2018)
The article considers the need to manage the financial potential of an insurance company. The analysis of optimization of the business process of financial support for the further development of the insurer has been carried out, deficiencies have been identified regarding the optimal option of attracting additional financial resources and measures for their correction have been developed.